Nino De Vita: poezja sycylijska między dialektalnością a zwierzęcością - Malicka, Paulina (Zoophilologica. Polish Journal of Animal Studies, 2016)
The purpose of this article is to draw attention to the issue of human-animal relationships in con- temporary works of poetry and prose by Nino De Vita (b. 1950) – a Sicilian born in Marsala, for whom the local dialect of Cutusìu contrade becomes the language of expression. The author leaves out of his writings anthropocentric models and introduces into them narratives concerning various forms of life marked by common and indivisible history. Both animal and human characters share similar fates, experience the same emotions, reciprocate feelings, suffer and feel fear. Still, what unites the human and animal world most is the language, or rather the dialect, of Marsala – a com- mon channel of interspecies communication. The expression of the animal nature in people who wish to most spontaneously and sincerely express their own emotions and moods, resorts to dialectal sound, the mother tongue, characterized by great intimacy but also violence. Finally, the dialectality and animality of Nino De Vita’s work involve going beyond the boundaries, tracking and leaving traces as well as marking the territory for fear of loss and being left. This poetry is written in the name of ‘another him’ and for him.